Weathering of pyrogenic organic matter induces fungal oxidative enzyme response in single culture inoculation experiments. (February 2016) - Gibson, Christy; Berry, Timothy D.; Wang, Ruzhen; Spencer, Julie A.; Johnston, Cliff T.; Jiang, Yong; Bird, Jeffrey A.; Filley, Timothy R.
Highlights: Weathered pyrogenic organic matter (PyOM) was exposed to the fungus T. versicolor . We investigated the interaction of this fungus with PyOM over a 36 d incubation. Weathered PyOM stimulated fungal respiration and enzymatic activity. No PyOM was mineralized during the incubation. Weathered PyOM positively primed medium-derived carbon. Abstract: The addition of pyrogenic organic matter (PyOM), the aromatic carbon-rich product of the incomplete combustion of plant biomass or fossil fuels, to soil can influence the rate of microbial metabolism of native soil carbon. The interaction of soil heterotrophs with PyOM may be governed by the surficial chemical and physical properties of PyOM that evolve with environmental exposure. We present results of a 36-day laboratory incubation investigating the interaction of a common white-rot fungus, Trametes versicolor, with three forms of 13 C-enriched (2.08 atom% 13 C) PyOM derived from Pinus ponderosa (450 °C): one freshly produced, and two artificially weathered (254 nm, UV light-water treatment and water-leaching alone). Analysis (FTIR, XPS) of the UV-weathered PyOM showed increased aliphatic C–H content and oxidation of aromatic carbon relative to both the original and water-leached PyOM. The addition of both weathered forms of PyOM stimulated (positively primed) fungal respiration of the growth media, while the unaltered PyOM mildly inhibited (negatively primed) respiration. Artificial weathering resulted in higher oxidative (laccase and peroxidase) enzyme activity than unaltered PyOM, possibly the result of a diminished capacity to bind reactive substrates and extracellular enzymes after weathering. However, and contrary to expectations, simple water-leached weathering resulted in a relatively higher enzyme activity and respiration than that of UV-weathering. The 13 C content of respired CO2 indicated negligible fungal oxidation of PyOM for all treatments, demonstrating the overall low microbial reactivity of this high temperature PyOM. The increased enzymatic and positive priming response of T. versicolor to weathered PyOM highlights the importance of weathering-induced chemistry in controlling PyOM–microbe–soil carbon interactions.